Economic burden and cost-effectiveness of treatments for open tibia fractures in Malawi: Economic analysis of a multicentre prospective cohort study - Alexander Thomas Schade; Linda Alinafe Sande; Ewan Tomeny; Maureen Sabawo; Nyamulani Nohakhelha; Kaweme Mwafulirwa; Leonard Banza Ngoie; Andrew John Metcalfe; David Griffith Lalloo; William James Harrison; Jason J. Madan; Peter MacPherson (PLoS ONE, 2025)
Background Open tibia fractures result in substantial lifelong disability for patients, and are expensive to treat. As the injury typically affects young working men, the societal costs from open tibia fractures are likely to also be high in low income countries, but remain largely unknown. We therefore investigated the overall societal costs and cost-effectiveness of different orthopaedic treatments at one year following an open tibia fracture in Malawi. Methods This study was a cost-utility analysis nested in a prospective cohort study from the healthcare- and societal-payer perspectives with a one-year time horizon. We obtained quality-adjusted life years (QALYs) from the EuroQoL 5 Dimension 3 Level (EQ-5D-3L) and patient lost productivity estimates at 6 weeks, and 3, 6, and 12 months post-injury. QALYs were calculated from utility scores were modelled within a hierarchical Bayesian multivariate modelling framework that jointly estimated individual-level trajectories in EQ-5D-3L scores and costs over follow-up. Direct treatment costs were obtained from a micro-costing study, and staff interviews at tertiary and district hospitals. Cost-effectiveness was reported in terms of societal cost per quality-adjusted life year (QALY). All costs were reported in 2021 United States dollars (USD). Results Between February 2021 and March 2022, 287 participants with open tibia fractures were included. There were substantial costs to participants one year following injury with 42% (n = 112) working with a median monthly household income of US$40 (IQR: US$7−90) compared to 89% (n = 255) working pre-injury, with a median monthly household income of US$60 (IQR: US$36−144). The posterior median of societal costs at one year varied between US$751 (80% credible intervals [CrIs]: US$-751−2,389) for treatment with plaster of Paris (POP) in a district hospital for a Gustilo III injury, to US$2,428 (80% CrIs: US$995−5027) for intramedullary nail in central hospital for a Gustilo III injury. The largest cost-effectiveness from a societal perspective was between an intramedullary nail and amputation for a Gustilo III injury with a posterior mean of US$2,290 (95%HDI: 36−4,547) per QALY. Conclusion The main finding was that open tibia fractures result in significant costs to patients, the healthcare system and society in Malawi. Although the funding of orthopaedic treatment can be difficult in countries with very limited healthcare budgets, the costs to society of ignoring this issue are very high. A re-balancing of health budgets (including from government and donors) is needed to prioritise trauma care to reduce the growing societal economic burden from injury.